Adjunctive efficacy of diode laser in the treatment of peri‐implant mucositis with mechanical therapy: A randomized clinical trial. Issue 5 (16th April 2019) - Aimetti, Mario; Mariani, Giulia Maria; Ferrarotti, Francesco; Ercoli, Elena; Liu, Chun Ching; Romano, Federica
Abstract: Objectives: Due to the inconclusive findings on the effect of laser therapy in the management of peri‐implant diseases, the aim of this study was to analyze the adjunctive clinical efficacy of 980‐nm diode laser (DL) irradiation in the treatment of peri‐implant mucositis with mechanical debridement. Material and methods: Two hundred and twenty patients with one implant diagnosed with peri‐implant mucositis (probing depth [PD] ≥ 4 mm and bleeding on probing [BoP] [primary outcome]) were randomly allocated to test and control treatments. Patients in the control group ( n  = 110) received debridement using curettes and ultrasonic devices, while patients allocated in the test group ( n  = 110) received mechanical therapy in combination with DL irradiation (setting 980 nm, 2.5 W, 10 kHz, pw, 30 s). BoP, presence of plaque, and PD were recorded at baseline, 1 month, and 3 months after treatment. Results: Both therapeutic modalities yielded similar clinical improvements with comparable reductions in the number of BoP‐positive sites, plaque scores, and PD values at 3 months (all p ‐values > 0.05). Complete disease resolution was obtained in 38/110 (34.5%) implants in the test group compared with 34/110 (30.9%) implants in the control group at the end of the observation period. Conclusion: Based on these results, the adjunct use of DL did not yield any statistically significant clinical benefit as compared to nonsurgical mechanical treatment alone in controlling peri‐implant inflammation at 3 months.